Distribution, habitat use mapping and conservation threats of fishing cat (Prionailurus viverrinus) in Shuklaphanta National Park, Nepal - Thanet, Dol Raj; Joshi, Laxmi; Sadadev, Bipana Maiya; Dhami, Bijaya; Kafle, Kopila (Polish Journal of Natural Sciences, 2022)
The fishing cat (Prionailurus viverrinus) is a medium sized wild cat of South and Southeast Asia. The Government of Nepal sponsors periodic monitoring of big cats and their prey species however, the population estimation of small cats including fishing cat is not yet estimated. In regards, we aimed to identify the current distribution status, habitat types used and existing conservation threat to fishing cat in Shuklaphanta National Park. Strip transect (1-2 km *5m) were laid and buffering was done within 1.5 km from the point of sign detected. Fishing cat was distributed in and around the wetland habitat in the form of patch. Further, we identified sal forest, riverine forest, sandy areas, grassland with marshy area and wetland with sparse sal forest as major habitat types. Using relative threat ranking method we identified over fishing, wetland depletion and lack of recognition of fishing cat habitat as critical threats.